The Efficacy and Safety of Cilostazol vs. Aspirin for Secondary Stroke Prevention: A Systematic Review and Meta-Analysis - Chai, Erqing; Chen, Jinhua; Li, Changqing; Zhang, Xue; Fan, Zhiqiang; Yang, Shijie; Zhao, Kaixuan; Li, Wei; Xiao, Zaixing; Zhang, Yichuan; Tang, Futian (Frontiers in Neurology, 2022)
Background: Cilostazol is often used in Asia-Pacific countries for stroke prevention. The current systematic review and meta-analysis aimed to evaluate the effectiveness, safety, and adverse outcomes of cilostazol monotherapy compared to aspirin monotherapy for secondary stroke prevention. Methods: The researchers conducted a comprehensive research in multiple databases (PubMed, Embase, and Coharance library) of randomized controlled trials from conception to December 2020. The primary efficacy outcome was the occurrence of any stroke, the primary safety outcome was the bleeding risk, and the primary adverse outcome was the rate of the headache and dizziness. The Mantel-Haenszel method was used to calculate a random-effects prediction. Cilostazol and aspirin were compared using a pooled risk assessments with 95 percent confidence intervals (CIs). Results: Sixeven studies involving patients were included in this review. Compared with aspirin monotherapy, cilostazol was associated with significantly lower rates of stroke (RR: 0.67; 95% CI: 0.55-0.82) and significantly lower hemorrhagebleeding rates (RR: 0.53; 95% CI: 0.37-0.74). However, compared with aspirin monotherapy, cilostazol was associated with significantly higher rates of headache (RR: 1.77; 95% CI: 1.41-2.20) and dizziness (RR: 1.28; 95% CI: 1.08-1.52). Conclusions: Consistent with previous studies, cilostazol monotherapy is superior to aspirin monotherapy in reducing the rate of strokes and the hemorrhagebleeding risk after having a stroke. However, the use of cilostazol monotherapy is associated with several adverse life outcomes such as headaches and dizziness.